2013
DOI: 10.1371/journal.pone.0080194
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Disability 24-Months after Injury for Hospitalised and Non-Hospitalised Participants: Results from a Longitudinal Cohort Study in New Zealand

Abstract: IntroductionMost studies investigating disability outcomes following injury have examined hospitalised patients. It is not known whether variables associated with disability outcomes are similar for injured people who are not hospitalised.AimsThis paper compares the prevalence of disability 24 months after injury for participants in the Prospective Outcomes of Injury Study who were hospitalised and those non-hospitalised, and also seeks to identify pre-injury and injury-related predictors of disability among h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 34 publications
(55 reference statements)
2
62
1
1
Order By: Relevance
“…Disease and illness (40%) followed by accidents and injury (28%) are the main causes of disability for Mäori (Statistics New Zealand, 2015). Derrett et al (2013) noted that 19% of Mäori, both hospitalised and non-hospitalised, experience disability 24 months following an injury. These researchers also found Mäori experienced disability at a significantly higher rate than non-Mäori who are hospitalised.…”
Section: Mäori and Disabilitymentioning
confidence: 99%
“…Disease and illness (40%) followed by accidents and injury (28%) are the main causes of disability for Mäori (Statistics New Zealand, 2015). Derrett et al (2013) noted that 19% of Mäori, both hospitalised and non-hospitalised, experience disability 24 months following an injury. These researchers also found Mäori experienced disability at a significantly higher rate than non-Mäori who are hospitalised.…”
Section: Mäori and Disabilitymentioning
confidence: 99%
“…Decreases in injury-related mortality rates have contributed to an increased focus on the survivors of injury and their longer-term outcomes, functional abilities, disabilities and health-related quality of life (HRQoL) 13. Research in this area has expanded in the last 10–15 years, however, it also focuses on working age adults, and their predominant types of injury (eg, road trauma, interpersonal violence or work-related injuries) and outcomes relevant to the working age population (eg, return to work or study, loss of income or unemployment) 13 14…”
Section: Introductionmentioning
confidence: 99%
“…A recent report showed that the rate of health-related loss due to injury for Māori is at least twice that of non-Māori 21. We found that Māori have poorer outcomes 12 months after the sentinel injury,22 and are at 70% increased risk of disability 24 months after the sentinel injury compared to non-Māori 23. These findings are concerning and warrant urgent attention.…”
Section: Introductionmentioning
confidence: 78%
“…Of the POIS participants, 61% were male, 68% New Zealand European and 92% in paid employment prior to their sentinel injury 12. Participants had a range of sentinel injuries (eg, lower extremity fractures (17%), upper extremity dislocations, sprains or strains (14%), upper extremity fractures (17%) and intracranial injuries (4%));43 and 25% had been hospitalised within one week as a consequence of their sentinel injury 23…”
Section: Design and Methodsmentioning
confidence: 99%